2022
DOI: 10.3390/nu14091748
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Prevalence and Outcomes of Long-Term Nasogastric Tube Placement in Adults

Abstract: Tube feeding (TF) is commonly used for patients with severe swallowing disturbance, and patients with chronic dysphagia are often provided with a long-term nasogastric tube (NGT). However, nationwide epidemiological data on long-term NGT placement are limited. The present study identified the prevalence and outcomes of patients with long-term NGT placement in Taiwan. Data were obtained from the Longitudinal Health Insurance Database. Patients with NGT placement for more than 3 months between 2000 and 2012 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There is a dearth of epidemiological data for use of long-term NGT. A study in Taiwan done by Chung Hsu et al [ 45 ] showed that long-term NGT placement was associated with higher risk of mortality and comorbidities such as acute and chronic respiratory illnesses, especially in stroke patients. In acute stroke patients, it is common to use a NGT as the patients often have decreased consciousness and related dysphagia.…”
Section: Ngt and Nutritionmentioning
confidence: 99%
“…There is a dearth of epidemiological data for use of long-term NGT. A study in Taiwan done by Chung Hsu et al [ 45 ] showed that long-term NGT placement was associated with higher risk of mortality and comorbidities such as acute and chronic respiratory illnesses, especially in stroke patients. In acute stroke patients, it is common to use a NGT as the patients often have decreased consciousness and related dysphagia.…”
Section: Ngt and Nutritionmentioning
confidence: 99%
“…NGT feeding may suffice for patients requiring nutritional support for up to 4 weeks [5]. Extended utilization of an NGT can lead to various adverse events, such as nasal wing lesions, chronic sinusitis, gastroesophageal reflux, gastrointestinal bleeding, and aspiration pneumonia [6][7][8]. Therefore, for extended periods, the placement of a gastrostomy tube should be taken into consideration to avoid the side effects of long-term usage of NGT for nutrition supply [5].…”
Section: Introductionmentioning
confidence: 99%
“…This approach should enable the evaluation of the effectiveness of drug administration (the effective amount of drug administered), also pinpointing whether any concerns arise from the compounding process or the administration procedure. Pravastatin sodium was selected as the model drug because it is a widely prescribed medication for the elderly population (enteral tube feeding being more prevalent among the elderly [19,20]), and is exclusively available in Italy in tablet form [21]. Furthermore, our interest extended to understanding the potential influences that nutritional formulas could exert on the amount of drug reaching the gastroenteric tract, as an interaction leading to dose reduction cannot be ruled out a priori [9].…”
Section: Introductionmentioning
confidence: 99%